Adult obesity management in New Zealand general practice: a review - Ross Lawrenson; Lisette Burrows; Lynne Chepulis; Kimberley Norman (Journal of Primary Health Care, 2021)
ABSTRACT INTRODUCTIONObesity is an important issue that leads to further health complications, increases the strain on the national health system and lowers quality of life. There is little available information on obesity management to guide best practice in general practice, despite 32% of New Zealand adults reported to be obese. AIMTo review obesity management in New Zealand general practice. METHODSWe searched six online databases for peer-reviewed research about adult obesity management. Inclusion criteria were original research, a New Zealand adult sample aged 25–64 years with a body mass index (BMI) >30 (or >25 BMI if participants had comorbidities) with weight loss (kg) as a measurable outcome. RESULTSEleven articles were identified: nine studies reported statistically significant weight loss from baseline, and two studies reported no significant weight loss. Three studies used a Kaupapa Māori approach. Weight loss results ranged from 0.56 to 12.1kg. Weight loss interventions varied in strategy and suitability for individual patients. DISCUSSIONWe found that there are effective weight loss interventions available for primary health-care professionals to refer to. Although most interventions did produce some weight loss, patients may need more comprehensive interventions that include a combination of diet, exercise and behaviour modifications in culturally appropriate ways. Future research should aim to identify and mitigate potential barriers to obesity management in primary care, as well as develop comprehensive, multileveled interventions that are effective for the local population.